Analisis Sedimentasi Di Check Dam Study Kasus : Sungai Air Anak dan Sungai Talang Bandung Desa Talang Bandung, Kecamatan Sumber Jaya, Kabupaten Lampung Barat - Togatorop, Holong; Kusumastuti, Dyah I; Tugiono, Subuh (Universitas Lampung, 2016)
The river is a source of water that is accommodating and drain the water and material ingredientsbrought from the upstream. Problems which often occur in the upstream region is land erosioncausing sedimentation. The purpose of this study is: to determine the sediment rate and tocalculate filling time check dam of Air Anak River and Talang Bandung river.The location of this research is in the Air anak watershed and Talang Bandung watershed, SumberJaya Districts, Lampung Barat. Data needed in this research is suspended load sediment data,rainfall data, and water level data. The method used in this study is the prediction modelparametric approach to Universal Soil Loss Equation (USLE), measured sediment analysis,analysis of check dam age.From the analysis using USLE method it is found that the amount of sedimentation Air AnakWatershed is 3.306.3091 tons / year and sedimentation Talang Bandung Watershed is 6.913.3709tons / year. While the magnitude of the measured sediment sample is for the Air Anak Watershed is4.447.3193 tons / year with the sedimentation rate is 4.043.0175 tons / year and the amount ofsedimentation for Talang Bandung Watershed is 13.501.3716 tons / year with a sedimentation rateis 12 273 , 9742 tons / year. From the research results it can be known the age of check dams forAir Anak Watershed is 148 days and Talang Bandung Watershed is 73 days.Keywords: sedimentation, Air Anak watershed, Talang Bandung watershed, USLE methode